Reliability of the Hop Test and Asymmetry Index in University Athletes: A Cross-Sectional Study Assessing Injury Risk - KAYHAN, RECEP FATİH (My University, 2024)
This study aims to assess the reliability of hop tests among healthy university athletes and to identify leg asymmetries through these assessments. A cohort of 212 university athletes, active in sports, participated in the study. Hop tests, comprising four distinct procedures, were administered to evaluate lower extremity strength. The hop tests demonstrated high reliability, with reliability coefficients ranging from 0.704 to 0.990. Examination of asymmetry indices revealed mean values of 101.07%, indicative of symmetrical limb function among participants. Gender-based differences were notable in hop test results, particularly in the crossover hop test, which showed significant asymmetry (p<.05). Age-related variances were observed solely in the single-leg hop test (p<.05), while asymmetry indices did not significantly differ across age groups (p>.05). As a result, it can be concluded that strength imbalances between gender and age are important functions affecting explosive power and the hop test gives reliable results in measuring these parameters. Moreover, the study hints at a low risk of injury among athlete students, given the inferred association between asymmetry indices and injury risk. Engaging in tailored physical activities and sports-specific training regimens may foster and sustain normal limb symmetry, potentially mitigating injury risks. Keywords: Injury, jump, reliability, strength

Bu çalışmanın amacı, sağlıklı üniversite sporcularında hop testlerinin güvenilirliğini değerlendirmek ve bu değerlendirmeler aracılığıyla bacak asimetrilerini belirlemektir. Çalışmaya toplamda 212 sporcu öprenci katılım gösterdi. Alt ekstremite kuvvetini değerlendirmek için dört farklı prosedürden oluşan hop testleri uygulandı. Analiz sonuçlarında hop testin Türk sporcu öğrenci örnekleminde güvenirlik düzeyleri 0,704-0,990 arasında olduğu ve yüksek düzeyde güvenirliğe sahip olduğu belirlendi. Sporcu öğrencilerin asimetri indekslerine bakıldığında ortalamaların 101,07% olduğu ve bu grubun normal uzuv simetrisine sahip olduğu belirlendi. Sporcu öğrencilerin cinsiyetleri açısından hop test değerlerinde farklılıkların olduğu, asimetri indeksi açısından ise sadece çapraz atlamada fark oluştuğu görüldü (p<,05). Sporcu öğrencilerin yaşları ile hop test değerleri arasında negatif yönede anlamlı ilişkilerin olduğu (p<,05), asimetri indeksinde ise yaş açısından ilişkiye rastlanmadığı görüldü (p>,05). Sonuç olarak cinsiyet ve yaş arasındaki kuvvet dengesizliklerinin patlayıcı gücü etkileyen önemli fonksiyonlar olduğu ve bu parametreleri ölçede hop testin güvenilir sonuçlar verdiği çıkarımı yapılabilir. Asimetri indeksleri ile yaralanma riski arasındaki çıkarımsal ilişki göz önüne alındığında, çalışmamız sporcu öğrenciler arasında düşük bir yaralanma riskine işaret etmektedir. Bu bağlamda kişiye özel fiziksel aktivitelere veya antrenman programlarına katılmak, normal uzuv simetrisini teşvik edebilir ve sürdürebilir, bu da potansiyel olarak yaralanma risklerini azaltabilir. Anahtar Kelimeler: Güvenilirlik, kuvvet, sıçrama, yaralanma
Sporcu Üniversite Öğrencilerinde Hop Test ile Asimetri İndeksi Belirlemenin Güvenirliği: Yaralanma Riskini Değerlendiren Kesitsel Bir Çalışma
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Beden Eğitimi ve Spor; Social Sciences and Humanities; Education; Physical Education and Sports; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; EĞİTİM, BİLİMSEL DİSİPLİNLER; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; EDUCATION, SCIENTIFIC DISCIPLINES; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Injury; jump; reliability; strength